Model Organisasi Ideal Bagi Perguruan Tinggi Islam di Indonesia - Afiful Ikhwan (Ta'allum: Jurnal Pendidikan Islam, 2013)
The model of organization plays significant role in controlling the quality of Islamic higher education. In this matter, the model becomes the core of the managerial works to develop the theory of management. An ideal organization is the one which has clear job description, hierarchy of autonomy, and career development. Too formal organization cannot be organized well. Therefore, for higher Islamic education, the most suitable model is organic unbiropatology.